RAPID CONSOLIDATION OF A NANOCRYSTALLINE FeCrAlSi-Al2O3 COMPOSITES BY PULSED CURRENT ACTIVATED SINTERING - Du, Song-Lee; Ko, In-Yong; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Sang-Whan; Shon, In-Jin (INST PROBLEMS MECHANICAL ENGINEERING-RUSSIAN ACAD SCIENCES, 2011)
A high-density nanocrystalline 4.88Fe(0.41)Cr(0.26)Al(0.25)Si(0.08)-Al2O3 composite was consolidated by a high-frequency, induction-heated sintering (HFIHS) within two minutes from mechanically activated powders of Fe2O3, Cr, Si, and Al powders. The advantage of this process is that it allows very quick densification to near theoretical density and prohibits grain growth in nanostructured materials. The average grain sizes and hardness were investigated.
Keywords: POWDERS; ALLOY